The influence of speed and strength abilities on the overall endurance of children aged 13-14 years with different typologies - Polevoy, Georgiy (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study was to determine the effect of a set of speed-strength exercises on the development of general endurance in schoolchildren aged 13–14, taking into account the differentiated load. METHODS: The pedagogical experiment was conducted on the basis of secondary school 60 in Kirov, Russia. The study involved 40 schoolchildren from the 7th grade, who were differentiated into the control and experimental groups of 20 people in each class. Children from the control group (CG) were engaged in physical education according to the standard program, and children from the experimental group additionally performed exercises for the development of speed and strength abilities with different loads. The strength of the nervous system was determined by tapping test, speed-strength abilities were determined by tests – flexion and extension of the arms at the stop while lying on the floor, long jump from a place with a push with two legs, and lifting the torso from the supine position. Overall endurance was determined by the “3 km ski run” test. RESULTS: In the CG, there was an improvement of only 2–4%. In the experimental group, there were significant improvements of 11–16%. CONCLUSION: I f schoolchildren perform exercises for the development of speed and strength abilities at physical education classes at school every time, then not only the indicators of these abilities will improve, but also the indicators of the overall endurance of children aged 13–14 will improve. Our results allow us to supplement the standard physical education program at school and effectively develop the physical qualities of schoolchildren aged 13–14.